PERAN UKSW DALAM PENANGGULANGAN PEMANASAN GLOBAL MELALUI PENANAMAN POHON PADA OMB 2023 - Wijanarka, Tunjung (Universitas Kristen Satya Wacana Salatiga, 2023)
The influence of global warming on the climate crisis presents a significant challenge that affects not only governments but also communities and individuals at grassroots level. Relying solely on government actions as the primary solution for a better Earth is insufficient. Instead, we can see initiatives led by private organizations and individuals as important contributors to addressing the cimate crisis. For instance, emphasizing the importance of environmental conservation, such as tree planting, plays a key role in tackling this issue. As a demonstration of our commitment, during the 2023 Student Orientation (OMB) at Universitas Kristen Satya Wacana (UKSW), partnered with the Djarum Foundation Community Service (BLDF) to engage in tree planting activities across Salatiga. This endeavor also aligns with the United Nations Sustainable Development Goals (SDGs). One of the pivotal locations for tree planting was the Tingkir Tengah, Salatiga, an area characterized by arid and barren landscapes that urgently require collaborative efforts from the government, private sector, and society at large.